STRATEGY OF DEVELOPMENT POTENTIAL LAND TO INCREASING INVESTMENT IN CIAMIS REGENCY: STUDY AT REGENCY STRATEGIC AREA (KSK) CORRIDOR OF CIHAURBEUTI-CISAGA - Apri Budianto; Dani Usmar (Magister Manajement Studies Program, 2017)
This article aims to examine potential land potential development strategies in increasing the investment in Kabupaten Ciamis, in the Strategic Areas of the Cihaurbeuti-Cisaga Primary Road Corridor (KSK) Corridor. Prepare data and information potential development potential of potential land (asset area) in increasing the investment in Ciamis Regency, in District Strategic Areas (KSK) Cihaurbeuti-Cisaga Primary Artery Road Corridor which then made the master document of potential data center economic object. The Research Method used is the Analytical Hierarchy Process (AHP) is a functional hierarchy with the main input is human perception. With the hierarchy, a complex and unstructured problem is solved into its group, which is then organized into a hierarchical form. The result of this research is 4 (four) potential of potential land area located in District Strategic Area (KSK) of Cihaurbeuti-Cisaga Primary Artery Road Corridor. There are 3 (three) potential land (potential assets) that occupy position 3 (three ) Which has high potential to be developed, each of which is the Self-Supported Area in Ciamis urban village, Karangmulyan Cultural Heritage Area, Maleber Terminal Export Area. Potential development of potential land (asset area) located in the District Strategic Areas (KSK) of Cihaurbeuti-Cisaga Primary Artery Road Corridor can be implemented through offensive strategy, it is based on the SWOT analysis results Potential potential land (potential assets) The District Strategic Area (KSK) of the Cihaurbeuti-Cisaga Primary Artery Road Corridor is currently at a strong intenal and external factor position. Object conditions have the opportunity to be developed into a tourist area (city tour) and environmentally sustainable superior cultural attractions supported by various elements of strength and opportunity, and minimize weaknesses and threats.